2012
DOI: 10.1097/ta.0b013e3182754759
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of modern battlefield colorectal trauma

Abstract: Epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 14 publications
1
30
2
1
Order By: Relevance
“…However, when focused specifically on colorectal trauma, GSWs are the predominant wounding modality. 4,[11][12][13][14]23,24 In the current study, GSW was found to be an independent risk factor for fecal diversion on multivariate analysis. Conversely, blast injury was not found to be an independent risk factor for colostomy.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, when focused specifically on colorectal trauma, GSWs are the predominant wounding modality. 4,[11][12][13][14]23,24 In the current study, GSW was found to be an independent risk factor for fecal diversion on multivariate analysis. Conversely, blast injury was not found to be an independent risk factor for colostomy.…”
Section: Discussionmentioning
confidence: 88%
“…[6][7][8][9] While DCS undoubtedly saves lives when judicially applied, how the well-established practice of fecal diversion relates to the newer wartime damage control techniques remains uncertain. 4,[10][11][12][13][14] Both primary colonic repair or resection with anastomosis carry increased morbidity in the wartime and civilian trauma setting, particularly when combined with DCS techniques. 10,[14][15][16][17] An initial step toward improving combat casualty care is understanding the wound and patient factors that correlate with colostomy creation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On multivariate analysis, significant predictors for stoma creation were rectal involvement (odds ratio (OR) = 2.2, rectum versus left colon; OR = 7.5, rectum versus right colon), gunshot wounds (OR = 3.4), Injury Severity Score ≥ 16 (OR, 1.7), and damage control surgery (OR, 1.6) [17]. The results of Glasgow et al, which present 977 coalition military personnel registered during eight years with colorectal injuries, should be noted [18]. The authors found that mortality was significantly higher for rectal injuries managed without fecal diversion (10.8% versus 3.7%, p < 0.0001) [18].…”
Section: Discussionmentioning
confidence: 99%
“…Glasgow et al [26] investigated 977 CRI cases and found that diversion rate in rectal injuries was approximately twice that in colon injuries. Similarly, rates in the present study were 90% and 36% in rectum and colon injuries, respectively.…”
Section: Discussionmentioning
confidence: 99%